Quantitation of Viral DNA by Real-Time PCR Applying Duplex Amplification, Internal Standardization, and Two-Color Fluorescence Detection - Gruber, Franz (American Society for Microbiology, 2001)
A real-time PCR method was developed to quantitate viral DNA that includes duplex amplification, internal standardization, and two-color fluorescence detection without the need to generate an external standardization curve. Applied to human parvovirus B19 DNA, the linear range was from 10(2) to at least 5 × 10(6) copies per ml of sample. The coefficient of variation was 0.29 using a run control of 2,876 copies per ml. The method reduces the risk of false-negative results, yields high precision, and is applicable for other DNA targets.